Atomic-scale observation of defects motion in van der Waals layered chalcogenide based materials. (June 2019) - Lotnyk, Andriy; Dankwort, Torben; Hilmi, Isom; Kienle, Lorenz; Rauschenbach, Bernd
Abstract: Ge-Sb-Te based alloys exhibit unique material properties and are used as active layer for data storage in phase-change memory technology. Interfacial phase-change memory based on chalcogenide superlattices are considered as a promising approach for further engineering of memory devices with lower power consumption. The internal bonding and the nature of layered defects in the superlattices are very similar to those observed in layered van der Waals (vdW) bonded Ge-Sb-Te structures. In this regard, uncovering the dynamic of such defects is crucial for a better comprehension of local structural transformations in those layered compounds. In this work, atomic-scale motion of bilayer defects is directly observed using in situ heating experiments inside an aberration-corrected scanning transmission electron microscope. The observations show lateral movements and self-reconfiguration of bilayer defects at elevated temperatures. These structural changes result in the local reorganization of vdW gaps and in an increase of overall structural order in layered Ge-Sb-Te materials. The present findings reveal the mechanism of structural reconfiguration in vdW layered Ge-Sb-Te materials and is assumed to be general in a wide range of similar layered compounds. Graphical abstract: Reconfiguration of van der Waals gaps in layered Ge-Sb-Te structure through motion of bilayer defects upon in-situ TEM heating.Unlabelled Image